THE DEVELOPMENT STRATEGY OF FASHARKAN LANTAMAL IX XYZ FROM CLASS C FASHARKAN TYPE TO FASHARKAN CLASS A KOARMADA III WITH SWOT AND ISM APPROACH - Rachmania Fajar; Abdul Rahman; Anton Nugroho (Indonesian Naval Technology College STTAL, 2020)
ABSTRACT The formation of Koarmada III resulted in a shift and an increase in the number the KRI in its working area, so it must be balanced with the ability of maintenance and repair facilities (fasharkan). Fasharkan XYZ is a fasharkan with class C status so it needs to be upgraded to class A in order to support its main task. The purpose of this research is to determine the alternative development strategy of Fasharkan XYZ. This study uses an integrated SWOT analysis and Interpretative Structural Modeling (ISM). SWOT analysis to formulate alternative strategies developed, namely the SO strategy consisting of 6 (six) strategic steps, the ST Strategy consisting of 6 (six) strategic steps, the WO Strategy consisting of 9 (nine) strategic steps and the WT strategy consisting of 4 (four) strategy move. From the weighting of the EFAS and IFAS matrices the WO strategy was selected. By using ISM, it is obtained 5 (five) levels of hierarchical structure from the classification of elements in the WO strategy, including the strategy (WO5) at level V. Then the sub strategies (WO1) and (WO4) are at level IV. At level III it consists of 4 (four) sub strategies, namely (W O2); (WO6); (WO7); (WO8). At level II, namely the sub strategy (WO3). At level I sub strategy (WO9). Keywords: Fasharkan XYZ, development strategy, SWOT, ISM.